Revisiting the Estimate of the North Sea Air‐Sea Flux of CO2 in 2001/2002: The Dominant Role of Different Wind Data Products. Issue 5 (9th May 2018) - Meyer, Maybritt; Pätsch, Johannes; Geyer, Beate; Thomas, Helmuth
Abstract: For the North Sea, a semienclosed shelf sea in the northeastern North Atlantic, the seasonal and annual CO2 air‐sea fluxes (ASF) had been estimated for 2001 and 2002 in earlier work. The underlying observations, Δ p CO2, salinity, and temperature had been combined with 6‐hourly wind data derived from ERA40 reanalysis. In order to assess the impact of different wind data products on the computation of CO2 ASF, we compared ERA40 wind data with coastDat data derived from the nonhydrostatic regional climate model COSMO‐CLM. From the four observational months September, November, February, and May all but the May data show higher wind speeds for coastDat than for ERA40, especially off the Norwegian, UK, and continental coasts. Largest differences occur in the northern offshore areas. The comparison with observed wind data supports this feature generally: At Helgoland, an island in the German Bight, and at the Belgium pile "Westhinder" the ERA40 data underestimate both, the coastDat data and the observations. Wind observations for two Norwegian North Sea platforms were available: At the northern station "Troll" off the Norwegian coast the coastDat data overestimate the observations in winter. At "Ekofisk" in the central North Sea the ERA40 data fit the observations well, while the coastDat data slightly overestimate the observational data in all months but in May. The corresponding CO2 ASF estimates show strongest deviations off the Norwegian coast. Using different bulk formulas for determining the net annual ASF resulted in differences due to different wind products of up to 34%. Plain Language Summary: Climate change is induced by gases like carbon dioxide, which are added to the atmosphere. The increase of the concentration in the atmosphere is dampened by the uptake of this gas by land and ocean. Especially, the coastal ocean is able to efficiently absorb CO2 . To calculate the North Sea‐wide uptake of CO2, simulated wind speed data were used. The formerly used model data cover the total Earth and thus have a less fine resolution. Especially near the coast this effect becomes dominant, as wind over land is more efficiently retarded than over sea. A new wind product (coastDat) with a refined grid was established especially for coastal applications. We compare the old and the new data with observational data sets. It has shown that the coastDat data are closer to observations near the coast. The old data set significantly underestimates the observational data there. At the open sea the new data set slightly overestimates the observations. The comparison of the mean flux of CO2 from the atmosphere into the ocean revealed an increase of 34% when using the new wind data instead of the old one. Key Points: The use of the new wind product coastDat increases the earlier estimated CO2 uptake flux in coastal areas of the North Sea (0.72 mol C·m ‐2 ·yr ‐1 ) by 0.88 mol C·m ‐2 ·yr ‐1 Comparisons with observations show that for coastal areas coastDat appears more suitable than ERA40 In the light of ongoing ocean acidification and warming a refinement of marine p CO2 observations bears the larger potential to reduce uncertainty of the CO2 flux estimates than further refinement of wind products